(untitled) (Indian Journal of Arid Horticulture, 2013)
Clonal propagation through micropropagation is hailed as a revolutionary technology as it can be achieved in a short time and space with limited number of plant propagules. Recent studies have shown that cell or tissue cultures undergo frequent genetic changes. Variants selected in tissue cultures have been referred to "somaclonal variation". Though, genetic variations may be considered obstructive and worthless from the point of clonal fidelity, it opens a window of opportunity for increased genetic variability relatively rapidly and without applying a sophisticated technology, which may itself have numerous applications in plant breeding and genetic improvements. The recovery of novel variants can be enhanced by applying suitable in vitro selection pressure. Tissue culture induced somaclonal variation in fruit crops is similar to variations induced with chemical and physical mutagens, which proffers an opportunity to unearth natural variability for their potential utilization in crop improvement.